Favorable Genotypes of Type III Interferon Confer Risk of Dyslipidemia in the Population With Obesity - Xu, Tiantian; Peng, Bo; Liu, Mengmeng; Liu, Qingjing; Yang, Junya; Qu, Minli; Liu, Na; Lin, Lizhen; Wu, Jing (Frontiers in Endocrinology, 2022)
Abstract Background: Studies have indicated that the chronic state of inflammation caused by obesity leads to dyslipidemia. However, how the polymorphisms involved in these inflammatory pathways affect the lipid metabolism in people with obesity is poorly understood. We investigated the associations of inflammation-related gene polymorphisms with dyslipidemia in individuals with obesity living in China. Methods: This case–control study in a population with obesity involved 194 individuals with dyslipidemia and 103 individuals without dyslipidemia. Anthropometric indices of obesity, fasting plasma glucose, blood pressure, blood lipids, and C-reactive protein were evaluated. The genes we tested were IL6 (interleukin 6), IL6R (interleukin 6 receptor), FOXP3 (forkhead box P3), TLR2 (toll-like receptor 2), TLR4 (toll-like receptor 4), IFNL3 (interferon lambda 3, formerly known as IL28B), and IFNL4 (interferon lambda 4, formerly known as IL29). Polymorphisms were genotyped using matrix-assisted laser desorption/ionization-time of flight mass spectrometry. Results: There were significant differences in the allelic and genotype frequencies of IFNL3 (IL28B) rs12971396, rs8099917, rs11882871, rs12979860, rs4803217 between non-dyslipidemia and dyslipidemia groups in people with obesity. These single nucleotide polymorphisms (SNPs) of IFNL3 were highly linked (D′ and r > 0.90), so the result of one SNP could represent the result of other SNPs. For IFNL3 rs12971396, people with the homozygous genotype (the major group) carried a higher risk of dyslipidemia than people with the heterozygous genotype (P < 0.001, OR = 4.46, 95%CI, 1.95–10.22). Conclusions: The favorable genotypes of type III interferon, which have a beneficial role in anti-virus function, were associated with dyslipidemia in a Chinese population with obesity. Type III interferon could have a pathologic role and confer risk of dyslipidemia in people with obesity and chronic inflammation.